2011
DOI: 10.1007/s00005-011-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism Disorders and the Risk of Cancer

Abstract: Diabetes and cancer are diseases which take the size of an epidemic spread across the globe. Those diseases are influenced by many factors, both genetic and environmental. Precise knowledge of the complex relationships and interactions between these two conditions is of great importance for their prevention and treatment. Many epidemiological studies have shown that certain types of cancer, especially gastrointestinal cancers (pancreas, liver, colon) and also the urinary and reproductive system cancers in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 180 publications
1
28
0
Order By: Relevance
“…For example, steroids or insulin play important roles not only in the function of reproductive organs and regulation of fluid homeostasis and/or metabolic pathways and immune responses to stress, but they are also involved in physiology, function and remodeling of bone, neuronal function, myelination and neurogeneration of brain and CNS and/or membrane-associated fatty acid metabolism (Bosch et al, 2002, Brunello et al, 2011, Campisi 2011, Chung et al, 2011, Goronzy and Wavand 2005, Hotamisisligil 2006, Khatami 1990, Li et al, 1986, Mikkola and Clarkson 2002, Sansoni et al, 2008, Simon and Balkau 2010, van Kruijsdijk et al, 2009). Insulin deficiency, insulin-resistance or hyper-insulinimia, or glucose toxicity and hyperglycemia of diabetes-induced increased glycosylation of proteins (advanced glycation end-products-AGE and their receptors RAGE) are associated with disturbances in transport and metabolism of important nutrients (e.g., ascorbic acid, pyridoxal phosphate, myo-inositol, etc), increased oxidative stress, accumulation of ROS, and co-expression of pro-and anti-inflammatory mediators such as NF-kB, VEGF, TNF-, IL1a, IL-6, IL-8, IL-12, and Ikappa B kinase (IKK-), platelets' CD40L, VCAM-1, in endothelial, hepatocytes or myeloid cells and/or tissues that are insulin-dependent (e.g., muscle, liver, adipocytes) or insulin-independent (e.g., vasculature, kidney, nerves, retina, RPE, lens) for glucose transport or metabolism , 1990, Li et al, 1986, Park et al, 2005, Pisan 2008, Piatkiewicz and Czech 2011, Simon and Balkau 2010, Stern et al, 2002. The relationship between diabetes, inflammation and production of AGE/RAGE and the increased risk of certain cancers has been the topic of many recent studies (Piatkiewicz and Czech 2011, Simon and Balkau 2010, Simon et al, 2010, Zhang and Hu 2010.…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, steroids or insulin play important roles not only in the function of reproductive organs and regulation of fluid homeostasis and/or metabolic pathways and immune responses to stress, but they are also involved in physiology, function and remodeling of bone, neuronal function, myelination and neurogeneration of brain and CNS and/or membrane-associated fatty acid metabolism (Bosch et al, 2002, Brunello et al, 2011, Campisi 2011, Chung et al, 2011, Goronzy and Wavand 2005, Hotamisisligil 2006, Khatami 1990, Li et al, 1986, Mikkola and Clarkson 2002, Sansoni et al, 2008, Simon and Balkau 2010, van Kruijsdijk et al, 2009). Insulin deficiency, insulin-resistance or hyper-insulinimia, or glucose toxicity and hyperglycemia of diabetes-induced increased glycosylation of proteins (advanced glycation end-products-AGE and their receptors RAGE) are associated with disturbances in transport and metabolism of important nutrients (e.g., ascorbic acid, pyridoxal phosphate, myo-inositol, etc), increased oxidative stress, accumulation of ROS, and co-expression of pro-and anti-inflammatory mediators such as NF-kB, VEGF, TNF-, IL1a, IL-6, IL-8, IL-12, and Ikappa B kinase (IKK-), platelets' CD40L, VCAM-1, in endothelial, hepatocytes or myeloid cells and/or tissues that are insulin-dependent (e.g., muscle, liver, adipocytes) or insulin-independent (e.g., vasculature, kidney, nerves, retina, RPE, lens) for glucose transport or metabolism , 1990, Li et al, 1986, Park et al, 2005, Pisan 2008, Piatkiewicz and Czech 2011, Simon and Balkau 2010, Stern et al, 2002. The relationship between diabetes, inflammation and production of AGE/RAGE and the increased risk of certain cancers has been the topic of many recent studies (Piatkiewicz and Czech 2011, Simon and Balkau 2010, Simon et al, 2010, Zhang and Hu 2010.…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
“…Insulin deficiency, insulin-resistance or hyper-insulinimia, or glucose toxicity and hyperglycemia of diabetes-induced increased glycosylation of proteins (advanced glycation end-products-AGE and their receptors RAGE) are associated with disturbances in transport and metabolism of important nutrients (e.g., ascorbic acid, pyridoxal phosphate, myo-inositol, etc), increased oxidative stress, accumulation of ROS, and co-expression of pro-and anti-inflammatory mediators such as NF-kB, VEGF, TNF-, IL1a, IL-6, IL-8, IL-12, and Ikappa B kinase (IKK-), platelets' CD40L, VCAM-1, in endothelial, hepatocytes or myeloid cells and/or tissues that are insulin-dependent (e.g., muscle, liver, adipocytes) or insulin-independent (e.g., vasculature, kidney, nerves, retina, RPE, lens) for glucose transport or metabolism , 1990, Li et al, 1986, Park et al, 2005, Pisan 2008, Piatkiewicz and Czech 2011, Simon and Balkau 2010, Stern et al, 2002. The relationship between diabetes, inflammation and production of AGE/RAGE and the increased risk of certain cancers has been the topic of many recent studies (Piatkiewicz and Czech 2011, Simon and Balkau 2010, Simon et al, 2010, Zhang and Hu 2010. It should also be noted that chronic inflammation in patients with neurodegenerative diseases, asthma or diabetes are reported to increase the risks for certain site-specific cancers (e.g., lung cancer in asthmatic patients, or liver and pancreas in diabetics) and decreased risk for certain other cancers (e.g., prostate in diabetics) (Brunello and Kappor 2011b, Piatkkiewicz and Czech 2011, Stern et al, 2002, Vena et al, 1985, Vesterinen et al, 1993, Vingeri et al 2009, Zhang and Hu 2010.…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
“…Diabetic patients have dysfunctional innate and adaptive immune systems, resulting in increased susceptibility to infections and subsequent development of immune system disorders (1,63,64). immune system dysfunction may ultimately lead to increased risk of cancer development.…”
Section: Dm Obesity and The Immune Systemmentioning
confidence: 99%
“…Prior studies demonstrated increased nK cellular activity in physically active individuals, especially athletes (1,(65)(66)(67). reduced activity was observed in individuals with high-fat diets.…”
Section: Dm Obesity and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation